English Language Acquisition by 6-Year-Old Child through Youtube Channel “Blippi” - Hamdani, Haris; Pudjiati, Danti; Tria Agustin , Dery (Darussalam English Journal (DEJ), 2025)
Language acquisition occurs in the acquisition of the second language, namely English language acquisition. Language is obtained because of the continuous practice factor. The aims of this study are to find out the process of English language acquisition by 6-year-old child through YouTube Channel “Blippi”, know the vocabularies mastered by 6-year-old child through YouTube Channel “Blippi”, and get information about the perception of child’s mother towards the 6-year-old child mastery of English vocabularies through YouTube Channel “Blippi”. This research uses qualitative methods with descriptive explanations. The results of this study found that the subject of this research gained a lot of vocabularies and had the ability to dialogue quite well using English. The results of the vocabularies spoken by the subject in this study were 8 fruits, 10 animals, and 5 vegetables. The subject's English language skills can be seen from his understanding of the shows he watched. His mother supports his language acquisition by providing the chances to her son to gain more English vocabularies through YouTube Channel “Blippi”.